5.7.3 Problems 201 to 300

Table 5.567: Solved using series method

#

ODE

Mathematica

Maple

1393

\[ {}\left (x^{3}+1\right ) y^{\prime \prime }+4 x y^{\prime }+y = 0 \]

1394

\[ {}x y^{\prime \prime }+y = 0 \]

1395

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+\alpha ^{2} y = 0 \]

1396

\[ {}y^{\prime }-y = 0 \]

1397

\[ {}y^{\prime }-x y = 0 \]

1398

\[ {}\left (1-x \right ) y^{\prime } = y \]

1399

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\alpha \left (\alpha +1\right ) y = 0 \]

1840

\[ {}\left (x +2\right ) y^{\prime \prime }+x y^{\prime }+3 y = 0 \]

1841

\[ {}\left (3 x^{2}+1\right ) y^{\prime \prime }+3 x^{2} y^{\prime }-2 y = 0 \]

1842

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }+\left (2-3 x \right ) y^{\prime }+4 y = 0 \]

1843

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+\left (2-x \right ) y^{\prime }+3 y = 0 \]

1844

\[ {}\left (3 x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+4 y = 0 \]

1845

\[ {}x y^{\prime \prime }+\left (2 x +4\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

1846

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-3 x y = 0 \]

1847

\[ {}\left (2-x \right ) y^{\prime \prime }+2 y = 0 \]

1848

\[ {}\left (1+x \right ) y^{\prime \prime }+2 \left (x -1\right )^{2} y^{\prime }+3 y = 0 \]

1849

\[ {}x^{2} \left (1-x \right ) y^{\prime \prime }+x \left (x +4\right ) y^{\prime }+\left (2-x \right ) y = 0 \]

1850

\[ {}x^{2} \left (1+x \right ) y^{\prime \prime }+x \left (2 x +1\right ) y^{\prime }-\left (4+6 x \right ) y = 0 \]

1851

\[ {}x^{2} \left (1+x \right ) y^{\prime \prime }-x \left (-x^{2}-6 x +1\right ) y^{\prime }+\left (x^{2}+6 x +1\right ) y = 0 \]

1852

\[ {}x^{2} \left (1+3 x \right ) y^{\prime \prime }+x \left (x^{2}+12 x +2\right ) y^{\prime }+2 x \left (x +3\right ) y = 0 \]

1853

\[ {}x^{2} \left (2 x^{2}+1\right ) y^{\prime \prime }+x \left (2 x^{2}+4\right ) y^{\prime }+2 \left (-x^{2}+1\right ) y = 0 \]

1854

\[ {}x^{2} \left (x^{2}+2\right ) y^{\prime \prime }+2 x \left (x^{2}+5\right ) y^{\prime }+2 \left (-x^{2}+3\right ) y = 0 \]

1855

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+6 x y^{\prime }+6 y = 0 \]

1856

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

1857

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-8 x y^{\prime }+20 y = 0 \]

1858

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-8 x y^{\prime }-12 y = 0 \]

1859

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }+7 x y^{\prime }+2 y = 0 \]

1860

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }+\frac {y}{4} = 0 \]

1861

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-5 x y^{\prime }-4 y = 0 \]

1862

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-10 x y^{\prime }+28 y = 0 \]

1863

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

1864

\[ {}y^{\prime \prime }+2 x y^{\prime }+3 y = 0 \]

1865

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }+y = 0 \]

1866

\[ {}\left (2 x^{2}+1\right ) y^{\prime \prime }-9 x y^{\prime }-6 y = 0 \]

1867

\[ {}\left (8 x^{2}+1\right ) y^{\prime \prime }+2 y = 0 \]

1868

\[ {}y^{\prime \prime }-y = 0 \]

1869

\[ {}y^{\prime \prime }-\left (x -3\right ) y^{\prime }-y = 0 \]

1870

\[ {}\left (2 x^{2}-4 x +1\right ) y^{\prime \prime }+10 \left (x -1\right ) y^{\prime }+6 y = 0 \]

1871

\[ {}\left (2 x^{2}-8 x +11\right ) y^{\prime \prime }-16 \left (x -2\right ) y^{\prime }+36 y = 0 \]

1872

\[ {}\left (3 x^{2}+6 x +5\right ) y^{\prime \prime }+9 \left (1+x \right ) y^{\prime }+3 y = 0 \]

1873

\[ {}\left (x^{2}-4\right ) y^{\prime \prime }-x y^{\prime }-3 y = 0 \]

1874

\[ {}y^{\prime \prime }+\left (x -3\right ) y^{\prime }+3 y = 0 \]

1875

\[ {}\left (3 x^{2}-6 x +5\right ) y^{\prime \prime }+\left (x -1\right ) y^{\prime }+12 y = 0 \]

1876

\[ {}\left (4 x^{2}-24 x +37\right ) y^{\prime \prime }+y = 0 \]

1877

\[ {}\left (x^{2}-8 x +14\right ) y^{\prime \prime }-8 \left (x -4\right ) y^{\prime }+20 y = 0 \]

1878

\[ {}\left (2 x^{2}+4 x +5\right ) y^{\prime \prime }-20 \left (1+x \right ) y^{\prime }+60 y = 0 \]

1879

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

1880

\[ {}y^{\prime \prime }-2 x y^{\prime }+2 \alpha y = 0 \]

1881

\[ {}y^{\prime \prime }-x y = 0 \]

1882

\[ {}\left (-2 x^{3}+1\right ) y^{\prime \prime }-10 x^{2} y^{\prime }-8 x y = 0 \]

1883

\[ {}\left (x^{3}+1\right ) y^{\prime \prime }+7 x^{2} y^{\prime }+9 x y = 0 \]

1884

\[ {}\left (-2 x^{3}+1\right ) y^{\prime \prime }+6 x^{2} y^{\prime }+24 x y = 0 \]

1885

\[ {}\left (-x^{3}+1\right ) y^{\prime \prime }+15 x^{2} y^{\prime }-36 x y = 0 \]

1886

\[ {}\left (2 x^{5}+1\right ) y^{\prime \prime }+14 x^{4} y^{\prime }+10 x^{3} y = 0 \]

1887

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

1888

\[ {}y^{\prime \prime }+x^{6} y^{\prime }+7 x^{5} y = 0 \]

1889

\[ {}\left (x^{8}+1\right ) y^{\prime \prime }-16 x^{7} y^{\prime }+72 x^{6} y = 0 \]

1890

\[ {}\left (-x^{6}+1\right ) y^{\prime \prime }-12 x^{5} y^{\prime }-30 x^{4} y = 0 \]

1891

\[ {}y^{\prime \prime }+x^{5} y^{\prime }+6 x^{4} y = 0 \]

1892

\[ {}\left (1+3 x \right ) y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

1893

\[ {}\left (2 x^{2}+x +1\right ) y^{\prime \prime }+\left (2+8 x \right ) y^{\prime }+4 y = 0 \]

1894

\[ {}\left (-2 x^{2}+1\right ) y^{\prime \prime }+\left (2-6 x \right ) y^{\prime }-2 y = 0 \]

1895

\[ {}\left (3 x^{2}+x +1\right ) y^{\prime \prime }+\left (2+15 x \right ) y^{\prime }+12 y = 0 \]

1896

\[ {}\left (x +2\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }+3 y = 0 \]

1897

\[ {}\left (x^{2}+3 x +3\right ) y^{\prime \prime }+\left (6+4 x \right ) y^{\prime }+2 y = 0 \]

1898

\[ {}\left (x +4\right ) y^{\prime \prime }+\left (x +2\right ) y^{\prime }+2 y = 0 \]

1899

\[ {}\left (2 x^{2}-3 x +2\right ) y^{\prime \prime }-\left (4-6 x \right ) y^{\prime }+2 y = 0 \]

1900

\[ {}\left (2 x^{2}+3 x \right ) y^{\prime \prime }+10 \left (1+x \right ) y^{\prime }+8 y = 0 \]

1901

\[ {}\left (x^{2}-x +1\right ) y^{\prime \prime }-\left (1-4 x \right ) y^{\prime }+2 y = 0 \]

1902

\[ {}\left (x +2\right ) y^{\prime \prime }+\left (x +2\right ) y^{\prime }+y = 0 \]

1903

\[ {}x^{2} y^{\prime \prime }-\left (6-7 x \right ) y^{\prime }+8 y = 0 \]

1904

\[ {}\left (2 x^{2}+x +1\right ) y^{\prime \prime }+\left (1+7 x \right ) y^{\prime }+2 y = 0 \]

1905

\[ {}\left (x +3\right ) y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }-\left (2-x \right ) y = 0 \]

1906

\[ {}y^{\prime \prime }+3 x y^{\prime }+\left (2 x^{2}+4\right ) y = 0 \]

1907

\[ {}\left (2+4 x \right ) y^{\prime \prime }-4 y^{\prime }-\left (6+4 x \right ) y = 0 \]

1908

\[ {}\left (2 x +1\right ) y^{\prime \prime }-\left (1-2 x \right ) y^{\prime }-\left (3-2 x \right ) y = 0 \]

1909

\[ {}\left (2 x +5\right ) y^{\prime \prime }-y^{\prime }+\left (5+x \right ) y = 0 \]

1910

\[ {}\left (x +4\right ) y^{\prime \prime }-\left (2 x +4\right ) y^{\prime }+\left (6+x \right ) y = 0 \]

1911

\[ {}\left (3 x +2\right ) y^{\prime \prime }-x y^{\prime }+2 x y = 0 \]

1912

\[ {}\left (2 x +3\right ) y^{\prime \prime }+3 y^{\prime }-x y = 0 \]

1913

\[ {}\left (2 x +3\right ) y^{\prime \prime }-3 y^{\prime }-\left (x +2\right ) y = 0 \]

1914

\[ {}\left (10-2 x \right ) y^{\prime \prime }+\left (1+x \right ) y = 0 \]

1915

\[ {}\left (7+x \right ) y^{\prime \prime }+\left (8+2 x \right ) y^{\prime }+\left (5+x \right ) y = 0 \]

1916

\[ {}\left (6+4 x \right ) y^{\prime \prime }+\left (2 x +1\right ) y = 0 \]

1917

\[ {}\left (\beta \,x^{2}+\alpha x +1\right ) y^{\prime \prime }+\left (\delta x +\gamma \right ) y^{\prime }+\epsilon y = 0 \]

1918

\[ {}\left (2 x^{2}+3 x +1\right ) y^{\prime \prime }+\left (6+8 x \right ) y^{\prime }+4 y = 0 \]

1919

\[ {}\left (6 x^{2}-5 x +1\right ) y^{\prime \prime }-\left (10-24 x \right ) y^{\prime }+12 y = 0 \]

1920

\[ {}\left (4 x^{2}-4 x +1\right ) y^{\prime \prime }-\left (8-16 x \right ) y^{\prime }+8 y = 0 \]

1921

\[ {}\left (x^{2}+4 x +4\right ) y^{\prime \prime }+\left (4 x +8\right ) y^{\prime }+2 y = 0 \]

1922

\[ {}\left (3 x^{2}+8 x +4\right ) y^{\prime \prime }+\left (16+12 x \right ) y^{\prime }+6 y = 0 \]

1923

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (2 x^{2}+3\right ) y = 0 \]

1924

\[ {}y^{\prime \prime }-3 x y^{\prime }+\left (2 x^{2}+5\right ) y = 0 \]

1925

\[ {}y^{\prime \prime }+5 x y^{\prime }-\left (-x^{2}+3\right ) y = 0 \]

1926

\[ {}y^{\prime \prime }-2 x y^{\prime }-\left (3 x^{2}+2\right ) y = 0 \]

1927

\[ {}y^{\prime \prime }+3 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

1928

\[ {}2 y^{\prime \prime }+5 x y^{\prime }+\left (2 x^{2}+4\right ) y = 0 \]

1929

\[ {}3 y^{\prime \prime }+2 x y^{\prime }+\left (-x^{2}+4\right ) y = 0 \]

1930

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

1931

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

1932

\[ {}\left (1+x \right ) y^{\prime \prime }+x^{2} y^{\prime }+\left (2 x +1\right ) y = 0 \]